The Patient was Returned at Demand In The Emerging Disease Case In Treatment Of Covid 19 Isolation In Indonesia - Bandiyah Marifah; Machli Riyadi (International Journal of Politic, Public Policy and Environmental Issues, 2022)
This study the legal status and legal consequences of patients returning home at their request in cases of Emerging diseases who are under Covid 19 isolation treatment in Indonesia. The type of research used is normative legal research. The approaches used in this legal research are the comparative approach, statute approach) and conceptual approach. The results of the study show that the patient's return at his request is the right of the patient with medical risks and legal consequences will be borne by the patient and or the patient's family. The legal consequences of a patient returning home from his request do not cause legal consequences, but the legal consequences arise when the patient is proven to be suffering from an infectious disease including an epidemic, he can be charged with the criminal provisions stipulated in the Law of the Republic of Indonesia Number 04 of 1984 concerning Infectious Plagues and State Law of the Republic of Indonesia Number 06 of 2018 concerning Quarantine.